700 Alumni entertained and celebrated for their contributions - UMP, PNC
Seven alumni of Universiti Malaysia Pahang (UMP) received honours under the Acclaimed Leadership Award introduced for the first time this year during the graduation dinner held in conjunction with its Sixth Convocation.